Strategi Mencapai Sustainabilty Bussiness Dengan Pelatihan Digitalisasi Keuangan Pada Pelaku UMKM Kota Magelang - Indrawati, Lucia Rita; Retnosari, Retnosari; Nilasari, Ayunda Putri; Sarwanti, Sri (Journal Of Human And Education (JAHE), 2024)
Problems faced by partners: (1) Still not maximized Accounting or financial records carried out by UMKM operators (2) The desire of the partner to carry out digital financial records that are expected to be able to assist financial records and are accessible anytime and anywhere (3) The expectation of a partner to have an organized accounting for his business. (4) The wish of the partners to arrange financial records for his or her business. From the problems faced by the partners, the dedication team undertook several activities as a solution to the problem. The first activity is to communicate how and the importance of accounting for business. Here the dedication team provides basic accounting material in general that can be used in the recording of business activity. Second Activity Provide applied training related to digitization of accounting for UMKM perpetrators using the financial system that has been prepared by the surveillance team. Here the dedication team provides training on the use of the Android-based Silapkeu system as a financial accounting container. With the help of Silapkeu, UMKM business finances become more organized because the system can generate financial reports and can be accessed whenever and wherever adapted to the needs of UMKM stakeholders. On the fourth activity, the dedication team performs support to UMKM agents so that their business becomes sustainable.